Characteristics of ground reaction force and frontal body movement during failed trials of single-leg lateral drop jump-landing task - Hirohata, K.; Aizawa, J.; Ohmi, T.; Ohji, S.; Yagishita, K. (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2021)
Background: /objectives: For biomechanical studies using jump-landing tasks, many researchers set the criteria for judging success or failure of the trial. Failed trials are usually removed from the analysis. However, the kinetics and kinematics during tasks included in failed trials might be important for understanding the mechanisms and risk factors of non-contact sports injuries. However, few studies have attempted to analyze failed trials. Therefore, the main objective of this study was to investigate the characteristics associated with ground reaction force (GRF) and two-dimensional frontal body movements during a failed trial of single-leg lateral drop jump-landing. Methods: Ten healthy women and 16 healthy men participated in this study. Spearman's rank correlation coefficients were calculated using the total number of failed trials and GRF data of successful trials. The association between frontal body movement and kinetics data was identified using correlation analyses. Wilcoxon signed-rank tests were performed to compare the GRF data of successful trials and failed trials of the same subject. Additionally, a two-way repeated measure analysis of variance was used to determine significant interactions of each trial and time after initial contact in the frontal body movement. Results: A total of 137 trials including successful and failed trials were recorded. There were 59 failed jump trials. There was a significant negative correlation between the number of failed jump trials and the elapsed time from initial contact to peak vertical GRF (peak vGRF time) during successful trials (r ¼ 0.427). The majority of failed trials were judged to be due to rearfoot movement patterns (rearfoot medial slip or rearfoot lateral slip). During rearfoot medial slip, we observed shorter peak vGRF time, larger trunk medial motions, and larger hip adduction movements after landing than that during successful trials. During rearfoot lateral slip, we observed larger trunk lateral motions and hip abduction movements after landing than that during successful trials. Conclusions: Athletes who frequently failed during single-leg lateral drop jump-landing had poor skills absorbing jump-landing impact, which is related to various sports injuries. It is possible to identify the risk factors for sports injuries by analyzing failure patterns.